Perivascular adipose tissue and the dynamic regulation of Kv7 and Kir channels: implications for resistant hypertension - Gollasch, Maik; Welsh, Donald G.; Schubert, Rudolf (Microcirculation, 2018)
Resistant hypertension is defined as high blood pressure that remains uncontrolled despite treatment with at least three antihypertensive drugs at adequate doses. Resistant hypertension is an increasingly common clinical problem in older age, obesity, diabetes, sleep apnea, and chronic kidney disease. Although the direct vasodilator minoxidil was introduced in the early 1970s, only recently has this drug been shown to be particularly effective in a subgroup of patients with treatment-resistant or uncontrolled hypertension. This pharmacological approach is interesting from a mechanistic perspective as minoxidil is the only clinically used K+ channel opener today, which targets a subclass of K+ channels, namely KATP channels in VSMCs. Beside KATP channels, two other classes of VSMC K+ channels could represent novel effective targets for treatment of resistant hypertension, namely Kv7 (KCNQ) and inward rectifier potassium (Kir2.1) channels. Interestingly, these channels are unique among VSMC potassium channels. First, both have been implicated in the control of microvascular tone by perivascular adipose tissue. Second, they exhibit biophysical properties strongly controlled and regulated by membrane voltage, but not intracellular calcium. This review focuses on Kv7 (Kv7.1-5) and Kir (Kir2.1) channels in VSMCs as potential novel drug targets for treatment of resistant hypertension, particularly in comorbid conditions such as obesity and metabolic syndrome.
First published: 06 December 2017
Im Titel sind die Buchstaben "v" und "ir" tiefgestellt
Gesehen am 09.05.2019